Conversion of Carbon Dioxide by Methane Reforming under Visible‐Light Irradiation: Surface‐Plasmon‐Mediated Nonpolar Molecule Activation. Issue 39 (13th August 2015) - Liu, Huimin; Meng, Xianguang; Dao, Thang Duy; Zhang, Huabin; Li, Peng; Chang, Kun; Wang, Tao; Li, Mu; Nagao, Tadaaki; Ye, Jinhua
Abstract A novel CO2 photoreduction method, CO2 conversion through methane reforming into syngas (DRM) was adopted as an efficient approach to not only reduce the environmental concentration of the greenhouse gas CO2 but also realize the net energy storage from solar energy to chemical energy. For the first time it is reported that gold, which was generally regarded to be inactive in improving the performance of a catalyst in DRM under thermal conditions, enhanced the catalytic performance of Rh/SBA‐15 in DRM under visible‐light irradiation (1.7 times, CO2 conversion increased from 2100 to 3600 μmol g−1 s−1). UV/Vis spectra and electromagnetic field simulation results revealed that the highly energetic electrons excited by local surface plasmon resonances of Au facilitated the polarization and activation of CO2 and CH4 with thermal assistance. This work provides a new route for CO2 photoreduction and offers a distinctive method to photocatalytically activate nonpolar molecules.